RELATIONSHIP OF WEIGHT GAIN, ANEMIA AND AGE WITH LOW BIRTH WEIGHT INFANTS - Irda Triyas Shanty; Rize Budi Amalia; Martono Tri Utomo (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: The incidence of LBW is still an important health problem because it contributes to infant mortality. There are several factors that influence the occurrence of LBW there are weight gain, anemia and mother’s age during pregnancy. The incidence of LBW in east java province in 2018 was 6,4%, this figure was 0,2% higher than the national rate. The purpose of this study to determine the relationship between maternal weight gain during pregnancy, anemia and mother’s age with low birth weight babies at RSUD Dr. M. Soewandhie Surabaya. Method: This study used an observational analytic method with a case control approach. Sampling with consecutive sampling technique. Sampling used medical record data for mothers giving birth in the delivery room of RSUD Dr. M. Soewandhie Surabaya in 2018. The sample of this study were 45 mothers giving birth to babies with low birth weight (LBW)and 45 mothers giving birth to babies with normal birth weight (BBLN). Data analysis used the chi-square test. Result: The results of the chi-square test analysis with α 0,05 showed that anemia in the mother (p = 0.02) related with low birth weight. Meanwhile maternal weight gain during pregnancy (p = 0.06) and the mother’s age (p = 1) were not related to LBW. Conclusion: These research showed that there is corelation beetween anemia and Low Birth Weight and there is no related beetween maternal weight gain and mother’s age on Low Birth Weight. Keywords: LBW, maternal weight gain, anemia, mother’s age